Analisis Puisi “Puisi Untuk Sriwijaya Air SJ 182” Karya Dwi Suranti dengan Menggunakan Pendekatan Mimetik - Legita Br Ginting (Lembaga Bale Literasi, 2024)
Literary works are not only a form of work that contains beauty, but literary works also contain meaning in them. Poetry is an imaginative literary work, structured in aesthetic and simple words but not easily understood by readers, especially without knowledge in analyzing poetry. Often the meaning of poetry is analogous to other objects so that the meaning of poetry is hidden behind the beauty of the words. Poetry can be a motivation for readers, especially those who love writing. Analysis of the poem